2022
DOI: 10.1002/hep4.1895
|View full text |Cite
|
Sign up to set email alerts
|

Male‐Specific Activation of Lysine Demethylases 5B and 5C Mediates Alcohol‐Induced Liver Injury and Hepatocyte Dedifferentiation

Abstract: Alcohol‐associated liver disease (ALD) is a major cause of alcohol‐related mortality. Sex differences in sensitivity to ALD are well described, but these are often disregarded in studies of ALD development. We aimed to define sex‐specific pathways in liver exposed to alcohol. Mice were fed the Lieber‐DeCarli alcohol liquid diet or a combination of a high‐fat diet with alcohol in water. Single‐cell RNA sequencing (scRNA‐Seq) was performed on liver cells from male and female mice. Mice were treated with adeno‐as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
0
20
2
Order By: Relevance
“…[ 27 ] We found that males and females dramatically differ in their response to alcohol, and we identified KDM5B and KDM5C as regulators of male/female differences, specifically male‐specific alcohol response in hepatocytes. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 27 ] We found that males and females dramatically differ in their response to alcohol, and we identified KDM5B and KDM5C as regulators of male/female differences, specifically male‐specific alcohol response in hepatocytes. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
“…Recently we performed scRNA‐seq analysis to identify sex‐specific pathways affected by alcohol in individual subsets of liver cells. [ 27 ] We found that males and females dramatically differ in their response to alcohol, and we identified KDM5B and KDM5C as regulators of male/female differences, specifically male‐specific alcohol response in hepatocytes. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations